2016
DOI: 10.1002/bimj.201600044
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of likelihood ratio tests and Rao's score test for three separable covariance matrix structures

Abstract: The problem of testing the separability of a covariance matrix against an unstructured variance-covariance matrix is studied in the context of multivariate repeated measures data using Rao's score test (RST). The RST statistic is developed with the first component of the separable structure as a first-order autoregressive (AR(1)) correlation matrix or an unstructured (UN) covariance matrix under the assumption of multivariate normality. It is shown that the distribution of the RST statistic under the null hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Moreover, to compare the obtained estimators with those commonly used in statistics, we determine the MLEs ( q Ψ) of the parameters of the considered covariance structures. Formulae for the MLEs of unknown components of CS and AR(1) can be found in Filipiak et al (2017). Since maximum likelihood estimation of a banded Toeplitz matrix is challenging and no explicit form of MLEs for T 1 and T 2 exist (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to compare the obtained estimators with those commonly used in statistics, we determine the MLEs ( q Ψ) of the parameters of the considered covariance structures. Formulae for the MLEs of unknown components of CS and AR(1) can be found in Filipiak et al (2017). Since maximum likelihood estimation of a banded Toeplitz matrix is challenging and no explicit form of MLEs for T 1 and T 2 exist (cf.…”
Section: Resultsmentioning
confidence: 99%
“…For CS and AR(1), the formulae described by Filipiak et al (2017) relating to the separable structure Ψ b Σ (Ψ : pˆp and Σ : qˆq) with q " 1 can also be used.…”
Section: Covariance Regularization Methodsmentioning
confidence: 99%
“…Complements, clarifications, adjustments, and corrections will continue to be made. The study of Soloveychik and Trushin (2016), which includes a nonrobust analysis section and an algorithm in the robust analysis section, is a superb example of this, and the RST for simple separability (Filipiak et al, 2016(Filipiak et al, , 2017) is a recent breakthrough on the testing side. In closing, most of the estimation and testing procedures discussed here are likelihoodbased and require normal distributions, which are rarely tested in practice.…”
Section: Discussionmentioning
confidence: 99%
“…238-289) and has been largely used with variance-covariance matrices (Muirhead, 1982). By definition, the statistic of the LRT is a ratio of two likelihoods: the maximum (supremum) of the likelihood function under H 0 , divided by the maximum (supremum) of the likelihood function under H. Secondly, Rao's score test (RST; Rao, 1984Rao, , 2005 has been much less used with variance-covariance matrices than the LRT, but may become popular soon in this context (Filipiak et al, 2016(Filipiak et al, , 2017. A complete description of the RST statistic is technical.…”
Section: Preamblementioning
confidence: 99%
“…The number of repeated measurements p is chosen as 3, 4, 5 and 7, and the number of characteristics q as 3. Filipiak et al [6] showed that the LRT as well as the RST statistics, respectively, do not depend on the choice of and ρ. Nevertheless, in this paper the 3 × 3 variance-covariance matrix is taken as =  2 1 2 1 4 3 2 3 5  and the correlation coefficient ρ of repeated measurements in the CS correlation structure is chosen as 0.5.…”
Section: Observed Type I Error Rates For Biased Lrt and Rst Statisticsmentioning
confidence: 98%